A Phenomenological Study on the Transformative Learning Experiences of International Students in Adult Education Graduate Programs - Qi Sun; Elizabeth Anne Erichsen (Adult Education Research Conference, 2008)
This phenomenological study endeavors to identify and illustrate international graduate students’ TL experience, to better inform our understanding of TL from a context of studying abroad and international students’ perspectives, and to foster transformative learning for international students
Keywords: transformative learning; international students; cross-cultural experiences